Pengaruh Politik Uang Terhadap Keputusan Memilih Caleg DPRD Dalam Pemilihan Umum Tahun 2024 di Kabupaten Pinrang - Hafid, umy_hafid02; Idham Irwansyah Idrus; Saifuddin (Jurusan Sosiologi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Lampung, 2025)
Money politics remains prevalent across all levels of electoral contests, where the public easily accepts gifts from candidates, risking the integrity of the democratic process. This phenomenon warrants thorough investigation to understand the forms of money politics during the 2024 election in Pinrang Regency and its influence on voters' decisions for Legislative Candidates (Caleg). This research employs a quantitative descriptive design with survey methods, supplemented by interview data. A simple cluster random sampling was used, with questionnaires completed by 99 respondents. Data were analyzed using simple regression techniques with SPSS software. The findings are interpreted through Social Exchange Theory and S-O-R (Stimulus-Organism-Response) theory, offering a novel approach compared to prior studies. Results indicate that forms of money politics in Pinrang including cash, basic necessities, and promises have a positive and significant correlation with voter decisions, with a probability value of 0.001 (below the 0.05 significance level). The correlation coefficient also signifies a fairly strong relationship between these variables. These findings highlight the critical need to enhance political literacy among the community and reinforce strong commitments from election organizers and participants to uphold democratic principles.